Analysis of Soil Related Constraints for Sustainable Intensification - World Agroforestry Centre; Sokoine University of Agriculture (International Food Policy Research Institute, 2015)
FAO estimates that agricultural intensification contributes about 80% of increased crop production in developing countries. Thus sustainable intensification (SI) will require, among other things, better use of land resources upon which production depends. This is critical given that most of the arable land in Africa has soil related problems, leading losses of nutrients and land cover (Heng et al. 2015). In this context improved land management is critical to overcoming soil related constraints to sustainable food production and in targeting agricultural interventions. However, limited availability of site-specific nutrient management guidelines for semi-arid zones in Tanzania undermines efforts to target technologies in the specific biophysical conditions in which smallholder farmers operate. Thus technologies adopted under these circumstances are risky as they may fail to address key drivers of enhanced crop production or land degradation. We characterized soils in Kongwa and Kiteto districts to assess fertility status and drivers of land degradation so as to inform the development of integrated land management options for SI under the Africa RISING project. This approach helps to link soil management recommendations to soil conditions and in targeting interventions. Project title: Africa RISING- Intensification of Maize-Legume Based Systems in the Semi-Arid Areas of Tanzania to Increase Farm Productivity and Improve Farming Natural Resource Base Project abstract: The aim of the Africa RISING project in Kongwa and Kiteto Districts, Tanzania is to provide a scientific basis for sustainably intensifying agricultural production in semi-arid areas of central Tanzania. The project activities are falls under 4 thematic areas that address three critical elements of sustainable intensification (SI), i.e. genetic, ecological and socio-economic intensification technologies. The scope of activities being implemented includes packaging of new legume and cereal varieties with over 120% yield advantage, packaging and validation of integrated productivity enhancing technologies for cereals, legumes, legume trees and soil health technologies, food safety primarily to reduce aflatoxin contamination and integration of livestock into the cropping systems. The innovation platform is used to set R4D priority in the active sites. In the 2013-2014 season, we reached out to about 1217 farmers Kongwa and Kiteto districts. In 2014 we plan to reach out to about 1500 new farmers. The project team is comprised of national partners (e.g. ARI-Hombolo, District Agricultural Officers, SUA and UDOM) and CG Partners (CIMMYT and ICRAF) under the leadership of ICRISAT. Project website: http://africa-rising.net